Preference of the vector thrips Frankliniella occidentalis for plants infected with thrips‐non‐transmissible Tomato spotted wilt virus. (20th August 2014) - Tomitaka, Y.; Abe, H.; Sakurai, T.; Tsuda, S.
Abstract The effect of a thrips‐non‐transmissible Tomato spotted wilt virus (TSWV) on insect–host interactions between thrips and Arabidopsis thaliana was analysed. A wild‐type TSWV virulent isolate and a TSWV isolate that induces mild symptoms on inoculated plants (TSWV‐Mo) were used in this study, and TSWV‐Mo isolate was obtained by single local lesion isolation using Petunia x hybrid after several passages on Nicotiana rustica plants. In transmission test, although wild‐type TSWV (TSWV‐wt) was transmitted by two thrips species (transmission ratio; Frankliniella occidentalis, 25%; Thrips tabaci, 10%; and T. palmi, 0%), none of the thrips transmitted TSWV‐Mo. Feeding damage by F. occidentalis in A. thaliana plants was more extensive on TSWV‐wt‐infected plants than on TSWV‐Mo‐infected plants, despite comparable preference. Among the markers of plant defences, salicylic acid‐regulated genes were upregulated threefold to sixfold by TSWV‐wt or TSWV‐Mo infection. In contrast, jasmonate‐regulated genes and jasmonate/ethylene‐regulated genes were not affected by the infections. Pull assays showed that adjacent TSWV‐Mo‐infected plants were preferred over uninfected plants. In conclusion, our results showed that the transmissibility by thrips of TSWV is not related to preference of vector thrips and suggested that TSWV‐Mo‐infected plants may be used as attractants for behaviour control of thrips.